Neuroregeneration and immune response after neurorrhaphy are improved with the use of heterologous fibrin biopolymer in addition to suture repair alone - Tibúrcio, Felipe Cantore [UNESP]; Muller, Kevin Silva [UNESP]; Leite, Ana Paula Silveira [UNESP]; de Oliveira, Igor Rodrigues Araújo [UNESP]; Barraviera, Benedito [UNESP]; Ferreira, Rui Seabra [UNESP]; Padovani, Carlos Roberto [UNESP]; Pinto, Carina Guidi [UNESP]; Matheus, Selma Maria Michelin [UNESP] (Wiley, 2023)
Introduction/Aims: Peripheral nerve injuries result in impaired neuromuscular interactions, leading to morphological and functional alterations. Adjuvant suture repair methods have been used to improve nerve regeneration and modulate the immune response. Heterologous fibrin biopolymer (HFB), a scaffold with adhesive properties, plays a critical role in tissue repair. The aim of this study is to evaluate neuroregeneration and immune response focusing on neuromuscular recovery, using suture-associated HFB for sciatic nerve repair. Methods: Forty adult male Wistar rats were distributed into four groups (n = 10): C (control), only sciatic nerve location; D (denervated), neurotmesis and 6-mm gap removal and fixation stumps in subcutaneous tissue; S (suture), neurotmesis followed by suture; and SB (suture + HFB), neurotmesis followed by suture and HFB. Analysis of M2 macrophages (CD206+), as well as the morphology and morphometry of nerves, soleus muscle, and neuromuscular junctions (NMJs), were performed at 7 and 30 days after surgery. Results: The SB group had the highest M2 macrophage area in both periods. After 7 days, SB was the only group similar to the C group regarding the number of axons; furthermore, after 30 days, the SB group was closer to the C group concerning blood vessel and central myonuclear numbers, NMJ angle, and connective tissue volume. After 7 days, increases in nerve area, as well as the number and area of blood vessels, were also observed in SB. Discussion: HFB potentiates the immune response, increases axonal regeneration, induces angiogenesis, prevents severe muscle degeneration, and assists in NMJ recovery. In conclusion, suture-associated HFB has major implications for improved peripheral nerve repair.
Keywords: heterologous fibrin sealant; immune response; nerve regeneration; neuromuscular junction; peripheral nerve injury